Contribution of clinical pharmacy to the rational and safe use of medicines in the neonatology unit of the pediatric university hospital Charles de Gaulle of Ouagadougou, Burkina Faso - Ouedraogo, Moussa; Pagbelguem, Bonsdawindé; Nikiema, Arsène Wendwaoga; Sombié, Charles B.; Ouedraogo, Emile W.; Zoungrana, Colette; Nagalo, Kisito; Kabore, Aïssata (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Newborns are exposed to drug therapeutic risks due to off-label prescribing and immaturity. The purpose of this study is to identify drug-related problems through the prescription and administration of drugs in the neonatology Unit and identify the need for pharmaceutical interventions. Methods: To assess drug-related problems, a cross-sectional observational study was conducted over five days at the neonatology Unit of the Pediatric University Hospital Charles de Gaulle in Burkina Faso. The study population consisted of newborns receiving drug prescriptions and treatment for five days. Results: Prematurity (50%) and early neonatal infection (53.3%) were the most common reasons for admission. A total of 380 prescription lines were recorded. Injectable and oral forms represented 72.1% and 26.3% respectively. Prescription lines in 16.8% were off-label medicines. An accuracy of drug dosages at 6.1% and an accuracy of prescribed doses at 52.7%, characterized therapeutic regimens. The prescribed drug administrations were performed in 80.0% with compliant doses and administration scheduled time 1 hour in 53.4 % and 54.6 %, respectively. Prescribers and nurses accepted 92.6% and 93.9% of proposed pharmaceutical interventions to solve drug-related problems. Conclusion. Our study emphasizes the importance of a clinical pharmacist within the health care team for the safe and efficient prescription and administration of newborn medication.